2019
DOI: 10.1039/c9em00310j
|View full text |Cite
|
Sign up to set email alerts
|

Assessing thermodynamic parameter sensitivity for simulating temperature responses of soil nitrification

Abstract: The sensitivity of SQRT model-estimated parameters varied over a temperature gradient whereas no variation in MMRT model-estimated parameters, in simulating temperature responses of soil nitrification over the temperature range, was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The soil samples, representing different soil types from different climate regions of Taiwan [41], were collected from cropped land and non-cropped land across four different counties including Chiayi, Taoyuan, Miaoli, and Pingtung. Six to eight soil samples from each site were collected randomly at depths of approximately 15 cm and a composite sampling technique was used to represent each sampled field.…”
Section: Soil Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The soil samples, representing different soil types from different climate regions of Taiwan [41], were collected from cropped land and non-cropped land across four different counties including Chiayi, Taoyuan, Miaoli, and Pingtung. Six to eight soil samples from each site were collected randomly at depths of approximately 15 cm and a composite sampling technique was used to represent each sampled field.…”
Section: Soil Samplingmentioning
confidence: 99%
“…An appropriate concentration of substrate (ammonium sulfate), which can provide an adequate amount of ammonium for AOA and AOB during the incubation period, and optimum concentration of Sodium chlorate (NaClO 3 ) to inhibit the oxidation of the nitrite was used as described in our previous study [41]. Mukhtar et al (2019) found no significant NO 2 − accumulation over 24 h above 200 mg L −1 of (NH 4 ) 2 SO 4 where NO 3 production was negligible above 7.5 mmol L −1 of NaClO 3 .…”
Section: Soil Incubation and Nitrification Potential Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQRT model simulated the maximum NP rates at 32 °C and the sudden drop in NP rates at 40 °C and thus, showed high NSE and correlation coefficient values for both organic and inorganic soils. However, the MMRT model showed high NSE and correlation constant values for soils that showed relatively less fluctuation in NP rates (smooth curve [43]) at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Mukhtar et al modeled the temperature-dependent soil nitrification potential rate with the square root model of Ratkowsky et al and estimated the optimum temperature for the nitrification potential rate with the heat capacity model. The authors suggest that the knowledge of thermodynamic properties of the soil nitrification response may be used to improve the application of large-scale fertilization, while reducing eutrophication and connected negative environmental impacts [105]. For cleaning purposes of contaminated water with excess nitrogen, denitrifying fixed-bed bioreactors can be used for NO 3 − removal [106].…”
Section: Application Of Temperature Models and Temperature For Biopromentioning
confidence: 99%